Reconciliation for the Settlement of Criminal Cases: Reactualization of Local Wisdom in Indonesian Criminal Law [Upaya Perdamaian Untuk Penyelesaian Perkara Pidana: Reaktualisasi Kearifan Lokal dalam Hukum Pidana Indonesia] - Rusjdi Ali Muhammad (Islamic Criminal Law Department, Faculty of Sharia and Law, UIN Ar-Raniry, 2021)
Abstract: One characteristic of Islamic law is not explicitly distinguished between the domain of public law and private law. Sanctions for deliberate murder are qishas for example, where the victim's heirs have a more permanent role to choose the death penalty imposed (qishas) or give forgive by request to pay diyat (compensation). Amount number of diyat is also can be negotiated through mediation method called Shulh (peace). So here the element of private law is more dominant. Even diyat can be released at all heirs of the victim initiatives. In this last case, the state may punish the offender with ta'zir, so here its public law elements recur. This idea is not unknown in Indonesian national law provisions. The victim had usually been involved as a witness in his father's murder case or rape case against her. In customary law in Aceh, there are several institutions in efforts to realize peace for criminal cases, namely in the form of adat meulangga, dhiet, sayam, or takanai (South Aceh). Principles of peaceful settlement of disputes may also be considered not only for civil cases but also in criminal cases. Thus, the doctrine that says the criminal nature of a case will not remove although there is a peace agreement, would need to be revisited. However, it is important also to restrict that not every criminal case could be solved by a peace agreement. Criminal cases like premeditated murder and rape should be excluded from the possibility of a peace agreement. Abstrak: Salah satu ciri hukum Islam adalah tidak secara tegas membedakan antara ranah hukum publik dengan hukum privat. Sanksi untuk pembunuhan yang disengaja adalah Qisas misalnya, dimana ahli waris korban memiliki peran yang lebih permanen untuk memilih hukuman mati yang dijatuhkan (Qisas) atau memberi maaf dengan meminta pembayaran Diyat (ganti rugi). Besaran jumlah Diyat juga dapat dinegosiasikan melalui semacam metode mediasi yang disebut Shulh (damai). Jadi di sini unsur hukum privat lebih dominan. Bahkan Diyat dapat dibebaskan pada semua ahli waris atas inisiatif korban. Dalam hal yang terakhir ini Negara dapat menghukum pelakunya dengan ta'zir, sehingga di sini unsur hukum publiknya terulang kembali. Gagasan ini tidak dikenal dalam ketentuan hukum positif Indonesia. Korban biasanya terlibat sebagai saksi dalam kasus pembunuhan ayahnya atau kasus pemerkosaan terhadap dirinya. Dalam hukum adat di Aceh terdapat beberapa lembaga dalam upaya mewujudkan perdamaian atas perkara pidana, yaitu berupa adat meulangga, dhiet, sayam atau takanai (Aceh Selatan). Prinsip-prinsip penyelesaian sengketa secara damai juga dapat dipertimbangkan tidak hanya untuk kasus-kasus perdata tetapi juga dalam kasus-kasus pidana. Dengan demikian doktrin yang mengatakan bahwa sifat pidana suatu kasus tidak akan hilang meskipun ada kesepakatan damai, perlu ditinjau kembali. Namun penting juga untuk membatasi bahwa tidak setiap kasus pidana dapat diselesaikan dengan kesepakatan damai. Kasus-kasus kriminal seperti pembunuhan berencana dan pemerkosaan harus dikesampingkan dari kemungkinan kesepakatan damai.